Spatial Distribution of Rice Planting Calendar in West Sumatra Province Based on MODIS Image Data - Ekaputra, Eri Gas; Yanti, Delvi; Irsyad, Fadly; Setyanto, Eri (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
Each region has its own cropping pattern due to its particular characteristics. Crop production may be increased by adjusting the timing of planting. Remote sensing technologies can be used to monitor regions where planting occurs simultaneously. The purpose of this study is to assess the degree of uniformity at the beginning of the paddy cultivation season in West Sumatra. In each growing season, there are two early cultivation seasons in the West Sumatra province. 19% of the region started cultivation in the first period of the first cultivation season (CS1), and 81% in the second period. 4.2% of the region started cultivation in the first period of the second cultivation season (CS2), while 95.8% started planting in the second period. 35% of the region started planting in the first period of the third cultivation season (CS3), while 65% started planting in the second period. The level of uniformity at the beginning of the second cultivation season was higher than at the beginning of the first cultivation season